2016
DOI: 10.1103/physrevc.94.064305
|View full text |Cite
|
Sign up to set email alerts
|

High-spin states in Al29 and Mg27

Abstract: The structure of 29 Al and 27 Mg was investigated using the reactions 18 O( 14 C,p2n) and 18 O( 14 C,α n) at 40 MeV. The charged particles were detected and identified with a ∆E-E telescope in coincidence with γ radiation detected in the Florida State University (FSU) Compton suppressed γ detector array. The level and decay schemes of both nuclei have been expanded at higher spins and excitation energies. The positive-parity states up to 3.5 to 4.5 MeV agree well with shell model calculations using the USDA in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…This motivated us to undertake the detail investigations on the level structure of 29 Al using a heavy-ion induced fusion evaporation reaction. Recently, Dungan et al [12] have reported results on the level structure of 29 Al using the 18 O( 14 C, p2n) reaction at an incident beam energy of 40 MeV. Indeed, the level scheme of 29 Al as deduced from the present measurement is similar to that of Dungan et al [12].…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…This motivated us to undertake the detail investigations on the level structure of 29 Al using a heavy-ion induced fusion evaporation reaction. Recently, Dungan et al [12] have reported results on the level structure of 29 Al using the 18 O( 14 C, p2n) reaction at an incident beam energy of 40 MeV. Indeed, the level scheme of 29 Al as deduced from the present measurement is similar to that of Dungan et al [12].…”
Section: Introductionsupporting
confidence: 82%
“…5/2 (J=5/2) (s 1/2 d 3/2 ) 3 (J=5/2) ] J=10/2 ). As mentioned earlier (see Table III), Dungan et al [12] placed a level at E x = 7263 keV which decays to the lower level members of Band-I through 1411-and 3688-keV transitions. From the present study, it is not possible to place the level in the level scheme because of the limited statistics in our data.…”
Section: Experimental Procedures and Data Analysismentioning
confidence: 82%
See 2 more Smart Citations
“…values in the range of 10 −2 to 10 −4 or less. This is consistent with previous observations [35,36]. As a test of these estimates, the neutron decay spectroscopic factor for the 6661 keV state was calculated in the shell model to be 0.0012, a factor of 2 above the upper limit in A bigger challenge is understanding the structure of the negative-parity states which must involve an odd number of particles outside the sd shell.…”
Section: Unbound Statessupporting
confidence: 68%